HEMODYNAMIC PARAMETERS OF PERIODONTAL TISSUES WITH PARTIAL SECONDARY ADENTIA (Modern American Journal of Biological and Environmental Sciences, 2026)
The paper examines the state of microcirculation of periodontal tissues of the supporting teeth and in the area of the dentition defect by laser Doppler flowmetry in patients with various dentition defects. The indicators of periodontal microcirculation have their own topographical features, which is confirmed by similar studies conducted earlier at the department.